Enhancement of English Language based-on the Cooperative Learning Model at Pondok Pesantren IMMIM Putra Makassar - Fawwaz, Nurkhalik Anang; Jannah, Izzatul; Febrianti, Riska (IJOCSE: Indonesian Journal of Community Services, 2025)
This community service project aimed to enhance English language proficiency among students at Pondok Pesantren IMMIM Putra Makassar through the implementation of a cooperative learning model. The program responded to the growing need for English communication skills in the era of globalization by introducing interactive, student-centered learning activities such as think-pair-share, group discussions, vocabulary games, and role-plays. Using qualitative methods—observation, in-depth interviews, and documentation study—the team found significant improvements in students' motivation, confidence, and active participation. The cooperative learning model proved effective in encouraging peer support, collaboration, and practical language use in real contexts. Both teachers and students positively perceived the program, noting its impact on fluency, vocabulary development, and student engagement. This initiative demonstrates that integrating cooperative learning strategies into language instruction in Islamic boarding schools can successfully promote meaningful English acquisition and 21st-century communication skills.